2016
DOI: 10.1080/21645515.2016.1151587
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B surface antibodies in medical students from a public university in Puebla, Mexico

Abstract: Although preventable with vaccination, Hepatitis B virus (HBV) infection is a major health concern, with »400 million people at risk of developing the chronic form of the disease worldwide. The anti-HBV vaccine consists of a recombinant HBV surface antigen (HBsAg), which induces specific anti-HBs antibodies and confers 95% protection for >20 y. The aim of the present study was to analyze the response to HBV vaccination by measuring anti-HBs antibodies in serum samples from medical students of a public universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…These findings can be attributed to the effectiveness of the vaccination program. In our study, the percentage of anti-HBs seropositive HCS was consistent with those reported in some other countries, such as Poland, Mexico, the United States, and Italy [22][23][24][25]; nevertheless, it was higher than the results of studies from Saudi Arabia, Taiwan, the United Arab Emirates, Italy, Spain, Palestine, and Iran [21,[26][27][28][29][30][31]. The anti-HB seropositivity of HCSs is widely distributed (17.0 to 89.4%) in Turkey [12,32,33].…”
Section: Sexsupporting
confidence: 91%
“…These findings can be attributed to the effectiveness of the vaccination program. In our study, the percentage of anti-HBs seropositive HCS was consistent with those reported in some other countries, such as Poland, Mexico, the United States, and Italy [22][23][24][25]; nevertheless, it was higher than the results of studies from Saudi Arabia, Taiwan, the United Arab Emirates, Italy, Spain, Palestine, and Iran [21,[26][27][28][29][30][31]. The anti-HB seropositivity of HCSs is widely distributed (17.0 to 89.4%) in Turkey [12,32,33].…”
Section: Sexsupporting
confidence: 91%
“…Several researches conducted among students attending healthcare courses highlighted the importance of measuring the immunological response against HBV and of the need for a booster dose in subjects with not protective values, since they have to be considered at higher risk of acquiring HBV infection due to traineeships and/or internships in hospital units [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been determined that 52% of health workers have been vaccinated at least once, but only 5.5% have complied with the complete scheme [ 29 ]. In the case of medical students, it was reported that 54% from a major university in Puebla had received at least one dose of the HBV vaccine, and more than 90% of those who received 2 or 3 doses had protective levels of anti-HBsAg [ 30 ]. Therefore, ideal levels of vaccine coverage have not yet been achieved in our population contributing to high prevalence, which could, in part, explain why the risk of iatrogenic transmission that we report here did not decrease further with NAT.…”
Section: Discussionmentioning
confidence: 99%